Linking Fiscal Policy to Economic Stability through Financial Sustainability - Muslim Muslim; Muh. Fadhel G Bata Ilyas; Amar Sani (Vifada Management and Social Sciences, 2024)
This study analyzes the role of fiscal policy and financial sustainability in enhancing economic stability, with a particular focus on developing economies facing fiscal constraints and macroeconomic uncertainty. The study aims to identify key dimensions of fiscal sustainability and examine how proactive fiscal policies, institutional reforms, and evidence-based strategies contribute to economic resilience. A qualitative systematic literature review (SLR) approach was employed by synthesizing empirical and theoretical studies published since 2018. Relevant peer-reviewed journal articles, policy reports, and institutional publications were analyzed to develop a multidimensional framework explaining the interaction between fiscal policy instruments and financial sustainability. The findings indicate that fiscal discipline, efficient and equitable taxation, and prudent public debt management are fundamental to maintaining financial sustainability. Proactive fiscal mechanisms, including automatic stabilizers and countercyclical spending, play a critical role in mitigating economic shocks and stabilizing macroeconomic performance during periods of crisis. However, developing economies continue to face significant challenges, such as limited fiscal space, weak institutional capacity, governance inefficiencies, and heavy reliance on external debt, which reduce the effectiveness of fiscal interventions. This study highlights the importance of institutional reforms to enhance fiscal transparency, strengthen public financial management, and improve accountability in order to build public trust and investor confidence. The research contributes to fiscal policy literature by offering an integrated framework linking fiscal sustainability and economic stability, while providing policy-relevant insights to support sustainable economic growth and long-term financial resilience.